2019
DOI: 10.1002/jbm.a.36623
|View full text |Cite
|
Sign up to set email alerts
|

Combinatorial effects of inorganic ions on adhesion and proliferation of osteoblast‐like cells

Abstract: Combinatorial effects of three ions, namely silicate (Si), calcium (Ca), and magnesium (Mg) ions, on the adhesion and proliferation of MC3T3‐E1 mouse osteoblast‐like cells were evaluated. The cells were cultured in single‐, dual‐, or triple‐ion‐conditioned culture media with systematically changed ion concentrations. The ranges of Si, Ca, and Mg ion concentrations were set as 10–70, 80–400, and 25–500 ppm, respectively. The numbers of adherent live cells were measured after culturing for 3 h and for 1, 3, and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 30 publications
(18 citation statements)
references
References 32 publications
(73 reference statements)
0
18
0
Order By: Relevance
“…However, during the rest of culture time, the PCL/GT and PCL/GT/GLN7% scaffolds' values overtook the PCL scaffold and even the control showing their great potential to provide a more suitable environment for the cells growth and proliferation. It is noteworthy that the scaffold containing the GLN nanoparticles exhibited more cells growth than the one without the nanoparticles rooting in the stimulating effects of GLN's ions like Ca and Si; these ions were reported to enhance osteoblast cells proliferation and differentiation 54,55 . The cell viability results showed that the ternary scaffold had greater potential for the cells growth than other scaffolds here.…”
Section: Resultsmentioning
confidence: 75%
See 1 more Smart Citation
“…However, during the rest of culture time, the PCL/GT and PCL/GT/GLN7% scaffolds' values overtook the PCL scaffold and even the control showing their great potential to provide a more suitable environment for the cells growth and proliferation. It is noteworthy that the scaffold containing the GLN nanoparticles exhibited more cells growth than the one without the nanoparticles rooting in the stimulating effects of GLN's ions like Ca and Si; these ions were reported to enhance osteoblast cells proliferation and differentiation 54,55 . The cell viability results showed that the ternary scaffold had greater potential for the cells growth than other scaffolds here.…”
Section: Resultsmentioning
confidence: 75%
“…However, at day 14, the PCL/GT/GLN7% scaffold had a higher ALP activity than other scaffolds and this trend was again repeated at the last time interval. The reason behind superiority of PCL/GT/GLN7% scaffold can be traced through the stimulating effects of Ca and Si ions on the osteoblast cells activity 54,55 …”
Section: Resultsmentioning
confidence: 99%
“…The concentration of extracellular Ca 2+ cations is a key factor for osteoblasts mineralization activity because the Ca 2+ is closely involved in the regulation of integrins ligand-binding processes and therefore mediation of adhesion, proliferation, and differentiation of cells in a matrix. [57] It was revealed that the increase of local concentrations of Ca 2+ results in enhanced osteoblasts adhesion, proliferation, and differentiation, which should promote their osteogenic activity. [58,59] Also, the vaterite can serve as a vehicle for bioactive species due to its high degree of porosity.…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies also proved that Mg 2+ with an appropriate concentration (50–200 ppm) can observably promote osteogenic differentiation and considerable new bone regeneration in bone defects [ 36 , 37 ]. Based on the above facts, Pan et al designed a macro-porous structured GelMA hydrogel with the incorporation of MgO nanoparticles (NPs) via thiol-ene click reactions [ 38 ].…”
Section: Hydrogels Crosslinked By the Physical Conditionsmentioning
confidence: 99%